Mineralogy and geochemistry of rare earth elements in the Moyil Valley alteration zones, Meshkinshahr (northwest Iran) - Naseri, Hossain; Jamadi, Mahnaz; Radmard, Kaikhosrov; Alavi, Ghafour (Geologos, 2020)
Sabalan Mountain (northwest Iran) witnessed intense volcanic activity during the Cenozoic (Plio-Pleistocene). The result of this manifests itself in the conical geometry of the Sabalan stratovolcano and ahigh hydrothermal gradient around it, which can be detected by geological phenomena such as hot springs, smoke gases and steam outlet pores. The high hydrothermal slope and upward migration of hot water in this area have caused extensive alteration zones in the host rocks. A mineralogical study of alteration zones in thewells drilled in the Moyil Valley to the northwest of Sabalan Mountain has revealed the presence of phyllic, argillic, calcitic and propylitic alterations in volcanic rocks (trachyandesite) and alteration phyllic and propylitic ones in monzonite rocks. In chondrite-normalised rare-earth-element diagrams, trachyandesite rocks exhibit an HREEs enrichment when compared to MREEs and LREEs in propylitic and calcitic alteration zones. This result can be explained by the acidic nature of hydrothermal fluids containing complex ions such as (SO-2, Cl-). The (La/Yb)cn, (La/Sm)cn and (Tb/Yb)cn ratios for argillic, phyllic, propylitic and calcitic alteration zones have revealed that they are higher in fresh rocks compared to altered rocks, suggesting the enrichment of HREEs in comparison to LREEs and MREEs. The anomalies of Eu do not change remarkably in the argillic and propylitic alteration zones of trachyandesite rocks; apparently, alteration hadno effect on them. Such behaviour reflects the presence of gold cations in Eu+3 formed at temperatures below 250°C. Eu anomalies increased in propylitic alteration zones in monzonite rocks and calciticand phyllic alteration zones in trachyandesiterocks.